2021
DOI: 10.1186/s40942-021-00324-6
|View full text |Cite
|
Sign up to set email alerts
|

Argus II retinal prosthesis for retinitis pigmentosa in the Middle East: The 2015 Pan-American Association of Ophthalmology Gradle Lecture

Abstract: Background To describe the outcomes of patients with retinitis pigmentosa (RP) who received the Argus II Retinal Prosthesis System. Methods This retrospective, interventional case series evaluated 10 consecutive patients who received the Argus II retinal implant and underwent visual function tests with the system on and system off. The main outcome measures were safety (the number, seriousness, and relatedness of adverse events), and visual functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The perceptual experience of clinically implanted Argus II patients has been variable ( Erickson-Davis and Korzybska, 2021 ). In many patients a significant proportion of electrodes cannot elicit percepts within safe current density limits ( Ahuja et al, 2013 ), and only limited pattern vision is generated by the device ( Stronks and Dagnelie, 2014 ; da Cruz et al, 2016 ; Arevalo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The perceptual experience of clinically implanted Argus II patients has been variable ( Erickson-Davis and Korzybska, 2021 ). In many patients a significant proportion of electrodes cannot elicit percepts within safe current density limits ( Ahuja et al, 2013 ), and only limited pattern vision is generated by the device ( Stronks and Dagnelie, 2014 ; da Cruz et al, 2016 ; Arevalo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…RP patients with mild visual impairment would not benefit from this device to restore normal vision [ 29 ]. However, a recent study has found that the safety profile of the Argus II has significantly improved compared to the pre-approval phase, with no significant issues reported up to four years post-implantation [ 30 ].…”
Section: Conventional Treatments and Limitationsmentioning
confidence: 99%
“…[27] Cerca del 50 % de pacientes con VRP tenía DRR total, hallazgo semejante al de Tseng et al [28] quien reporta que los DRR con compromiso de al menos 3 cuadrantes se asocian más a VRP. Además, encontramos que el tiempo de enfermedad en pacientes con VRP fue mucho mayor que en aquellos que no lo tenían, lo cual concuerda con la literatura que menciona que uno de los riesgos para la aparición de VRP es un DRR con más de 1 mes de evolución [29] .…”
Section: éXito Funcional a 6 Mesesunclassified